Maxillaria jostiiDodson (Orchidaceae) a new record for the Flora of Peru - Rodríguez Rodríguez, Eric F. (2013)
We present here to Maxillaria jostii Dodson (Orchidaceae) a new addition to the angiosperm Flora of Peru from sandstone substrate of the Sub-Andean Cordillera de Huarango (province of San Ignacio, department of Cajamarca), a southern prolongation to the very biodiverse Cordillera del Condor. Maxillaria jostiihas been formerly considered a species endemic to southern Ecuador (Zamora-Chinchipe, Morona-Santiago), but with the present study extends its geographical distribution range to northern Peru. This new contribution to the knowledge of the Flora of Peru is the result of a combined fieldwork and herbarium effort, thanks to Binational Project named “Botanical Inventory of the Cordillera del Condor Region of Ecuador and Peru, 2005-2007" and developed by the following scientific institutions: MO, HUT, LOJA and QCNE. The species reported here was compared against the list of species documented in the «Catalogue of Flowering Plants and Gymnosperms of Peru» (Brako & Zarucchi 1993) and «Ten years of additions to the flora of Peru: 1993-2003» (Ulloa Ulloa et al. 2004) and «Angiosperms additions to flora of Peru» (Rodríguez et al. 2006b).